THE IMPORTANCE OF NON-CASH PRACTICES IN STABILIZING THE PAYMENT SYSTEM AND WAYS TO SOLUTION EXISTING PROBLEMS - Normamatov , Ixtiyor (THE INNOVATION ECONOMY, 2023)
Ensuring the efficiency of using forms of non-cash payments is one of the prerequisites for the development of a non-cash payment system. Improving the practice of using non-cash forms of payment plays an important role in solving the problem of economic insolvency, ensuring the continuity of production activities of companies, and developing export-import operations. This, in turn, requires identifying current problems associated with improving the practice of using non-cash payment forms and developing ways to solve them. Currently, there are a number of problems associated with improving the practice of using non-cash forms of payment in our country. The article identifies problems associated with ensuring the efficiency of using forms of non-cash payments in the Republic of Uzbekistan and develops scientific proposals aimed at solving these problems.